Comparative study of nifepidine and isoxsuprine in suppression of preterm labour - Jain, Prerna; Suman, Supriya; Mishra, Manju Gita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: A prospective study was conducted to compare the efficacy of nifedipine against isoxsuprine in preventing preterm labour and also to evaluate maternal side effects and neonatal outcome. Methods: This was a randomized prospective comparative study done at MGM hospital and research center, Patna, Bihar between 15/03/2014 to 15/02/2016. 75 antenatal women with gestational age between 28 to 36 weeks were selected who fulfilled the inclusion criteria for the study, were given nifedipine and were monitored throughout the course of treatment. Results: Groups were compared with mean prolongation of delivery, side effects, neonatal outcome, parity, cervical effacements. Nifedipine was twice more effective than isoxsuprine hydrochloride as a uterine tocolytic agent while side effects were comparable with fewer side effects in nifedipine group. Neonatal outcome was better with nifedipine in comparison to isoxsuprine. Conclusions: There is a high incidence of preterm labour in India. The present study found that nifedipine has better tocolytic efficacy, less side effects and better tolerability as compared to isoxsuprine.